1990
DOI: 10.1161/01.cir.82.5.1629
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up of survival and myocardial infarction in the randomized Coronary Artery Surgery Study.

Abstract: The Coronary Artery Surgery Study (CASS) (Circulation 1990;82:1629-1646 T he Coronary Artery Surgery Study (CASS) sponsored by The National Heart, Lung, and Blood Institute is designed to assess the effect of coronary bypass surgery on mortality and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
2
12

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(150 citation statements)
references
References 19 publications
2
134
2
12
Order By: Relevance
“…Left internal thoracic artery conduits were used in only 14% of patients in the Coronary Artery Surgery Study. 3 CAD, 94% with normal ventricular function). Death or myocardial infarction occurred in 6.3% of PTCA patients and 3.3% of medical therapy patients (absolute difference, 3.0%; 95% confidence interval [CI], 0.4% to 5.7%; Pϭ0.02).…”
Section: Comments On First-generation Rctsmentioning
confidence: 99%
“…Left internal thoracic artery conduits were used in only 14% of patients in the Coronary Artery Surgery Study. 3 CAD, 94% with normal ventricular function). Death or myocardial infarction occurred in 6.3% of PTCA patients and 3.3% of medical therapy patients (absolute difference, 3.0%; 95% confidence interval [CI], 0.4% to 5.7%; Pϭ0.02).…”
Section: Comments On First-generation Rctsmentioning
confidence: 99%
“…In these two subgroups the improved survival with CABGS became statistically significant at the follow-up mark of 84 months. 26,27 However, during the next analysis (at 120 months) in the subgroup with LVEF <50% + 3-vessel involvement the survival benefit of CABGS was found not significant anymore. Except for these findings there was no difference in mortality between the treatment arms in patients subgrouped by 1v, 2v, or 3v involvement.…”
Section: Comparison Of Myocardial Revascularization With Medical Therapymentioning
confidence: 87%
“…27 However, further analysis of the CASS data in group-B patients (mild-moderate angina + LVEF >=35% but <50%) revealed improved mortality rates with CABGS compared to medical therapy. 26,27 Additionally, in the CASS study CABGS, compared to medical therapy, was associated with improved survival in the subgroup with LVEF <50% as well as in the subgroup with LVEF <50% + 3-vessel involvement. In these two subgroups the improved survival with CABGS became statistically significant at the follow-up mark of 84 months.…”
Section: Comparison Of Myocardial Revascularization With Medical Therapymentioning
confidence: 96%
See 1 more Smart Citation
“…12 As the applicability of PCI expanded, randomised data showed that surgical and percutaneous revascularisation were equivalent in terms of both survival and future risk of MI. 13 The latter strategy, however, would incorporate a greater likelihood of requiring a further intervention because of restenosis, but the introduction of routine stenting 14 -particularly with drug-eluting devices 15 -soon eroded this difference.…”
Section: The Evidence Basementioning
confidence: 99%